Finding chemo: the search for marine-based pharmaceutical drugs active against cancer - Indumathy, S.; Dass, Crispin (John Wiley & Sons Ltd., 2013)
Objectives: Cancer affects the health of many people globally. The most common treatment that is used for cancer is chemotherapy, which has shown promising results but not without side effects. Some of these side effects jeopardise further treatment, and this eventually leads to advanced stages of malignancy and mortality. As a result, there is a need for better and safer anticancer compounds such as those found naturally. One of the most abundant natural environments to find such compounds is the sea, and this vast resource has been biomined since the 1950s. Key findings: There are currently three marine anticancer agents marketed (Yondelis, Cytosar-U and Halaven), with several others undergoing clinical trials. This review discusses marine-derived products in clinical use and in clinical trials, and discusses available literature on the growth suppression or pro-apoptotic properties of these compounds, and the molecular mechanisms underpinning these cell biological phenomena. Summary: The marine environment may hold promising anticancer compounds within its depths, warranting further research to be performed in this area, albeit with respect for the natural ecosystems that are being explored for drug discover and subsequently used for drug development.